The Role of Social Work in the Oppression of Single Mothers by the Cultural Policy of the Neoliberal State - Radka Janebová (Gender a Výzkum, 2020)
The oppression of single mothers generally takes specific forms in neoliberal society, because the traditional pressure associated with the female caring role is accompanied by oppression derived from their dependence on the welfare system. Social work can play an important role in this oppression because, as one of the 'psy' professions, it becomes a tool of surveillance of fulfilment of the female caring role and aims to discourage women from dependency on welfare system at the same time. The aim of the article is to reflect the risk of oppression of single mothers from the Czech social work in the context of the cultural policy of the neoliberal state. The surveillance technologies used by social workers were sought through the analysis of Michel Foucault's work. It was found that the promotion of idea of human as homo oeconomicus plays a role in assessment process and in choosing the method of intervention. Other significant surveillance techniques may be the illusion of the neutral knowledge of the profession, the duty of confession and the gatekeeping.